Exercise medicine as adjunct therapy during RADIation for CAncer of the prostaTE to improve treatment efficacy – protocol for the ERADICATE study: a phase II randomised controlled trial - Oliver Schumacher; Robert U. Newton; Colin Tang; Raphael Chee; Sjoerd B. Vos; Ronny S. Low; David Joseph; Dennis R. Taaffe; Daniel A. Galvão (BMC Cancer)
Abstract Background Tumour hypoxia resulting from inadequate perfusion is common in many solid tumours, including prostate cancer, and constitutes a major limiting factor in radiation therapy that contributes to treatment resistance. Emerging research in preclinical animal models indicates that exercise has the potential to enhance the efficacy of cancer treatment by modulating tumour perfusion and reducing hypoxia; however, evidence from randomised controlled trials is currently lacking. The ‘Exercise medicine as adjunct therapy during RADIation for CAncer of the prostaTE’ (ERADICATE) study is designed to investigate the impact of exercise on treatment response, tumour physiology, and adverse effects of treatment in prostate cancer patients undergoing external beam radiation therapy (EBRT). Methods The ERADICATE study is a two-arm, parallel group, phase II randomised controlled trial. Fifty patients diagnosed with prostate cancer will be randomised (1:1) to either an exercise intervention group (EBRT + exercise) or a usual care control group (EBRT only) for the duration of treatment (i.e., 2 to 8 weeks of EBRT). The exercise intervention will be clinic-based and supervised by exercise physiologists. Exercise sessions will include moderate- to vigorous-intensity aerobic and resistance exercise conducted two to three times per week for 60 min per session. Treatment response (primary outcome) will be assessed by change in tumour apparent diffusion coefficient derived from magnetic resonance imaging. Secondary outcomes will include acute and chronic changes in tumour perfusion and hypoxia, treatment-related toxicity, body composition, physical function, and quality of life. Survival outcomes will be assessed as exploratory endpoints. Study measurements will be conducted at baseline (i.e., prior to commencing EBRT), immediately after completion of EBRT, and during follow-up at 3 months as well as 2 years and 5 years post treatment. The study was approved by the Human Research Ethics Committee at Edith Cowan University. Discussion The ERADICATE study will investigate exercise as a novel therapeutic approach for sensitising prostate cancer to EBRT by targeting a known mechanism of treatment resistance. Improving treatment efficacy of EBRT with exercise may result in better patient outcomes clinically, while also addressing adverse effects of treatment and quality of life in prostate cancer patients. Trial registration The study was registered on the Australian New Zealand Clinical Trials Registry (ACTRN12624000786594) on 26/06/2024.